2012
DOI: 10.1007/s10096-012-1655-1
|View full text |Cite
|
Sign up to set email alerts
|

Implantable electrophysiologic cardiac device infections: a risk factor analysis

Abstract: The risk of cardiac device infection (CDI) is rising significantly, with several risk factors identified. The purpose of this study is to determine the rate of CDI at our center and to assess the associated risk factors, in order to define appropriate measures to prevent this complication. We retrospectively reviewed all cases of patients with CDI at St. George Hospital between February 1999 and July 2010. Each case was matched with three controls. We performed a descriptive and bivariate analysis to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 29 publications
4
29
0
1
Order By: Relevance
“…Generator pocket hematoma is a complication of CIED placement. Prevention of hematoma is desirable as it prolongs hospitalization, and requires need for further surgery for hematoma evacuation, and associated with increased risk of infection . The risk of pocket hematoma in patients being bridged with heparin around the time of CIED placement is significant, 17–31%, and therefore the use of heparin should be avoided …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generator pocket hematoma is a complication of CIED placement. Prevention of hematoma is desirable as it prolongs hospitalization, and requires need for further surgery for hematoma evacuation, and associated with increased risk of infection . The risk of pocket hematoma in patients being bridged with heparin around the time of CIED placement is significant, 17–31%, and therefore the use of heparin should be avoided …”
Section: Discussionmentioning
confidence: 99%
“…and requires need for further surgery for hematoma evacuation, and associated with increased risk of infection. 4,[29][30][31] The risk of pocket hematoma in patients being bridged with heparin around the time of CIED placement is significant, 17-31%, and therefore the use of heparin should be avoided. 4,32 In our survey, we found approximately one-third of responders either bridged with low-molecular-weight heparin (37.1%), unfractionated heparin (31.8%), or they stop warfarin and do not bridge (31.2%).…”
mentioning
confidence: 99%
“…36,44,55,56 This is particularly important as several precautions can be taken to reduce the peri-operative bleeding risk. Anticoagulants are associated with an increased risk of DRI, 36, 43 and a balance must therefore be struck between the risk of peri-operative bleeding and that of thrombo-embolic events.…”
Section: Procedural Related Factorsmentioning
confidence: 99%
“…78 Although infrequent, an abdominal implant will on occasion be indicated and it should be recognized that these confer a higher risk than standard pre-pectoral implants (0.5% versus 3.2%). Every effort should be made to avoid post-operative hematoma formation, 36,44,55,56 and meticulous attention to hemostasis is essential. Hemostasis is readily achieved by the use of diathermy and hemostatic sutures though there are no data to specifically support that this practice reduces infection.…”
Section: Operative Considerationsmentioning
confidence: 99%
“…Specifically, 1‐year follow‐up results from the Bridge or Continue Coumadin for Device Surgery Randomized Controlled Trial (BRUISE CONTROL) showed that the risk of device infection was more than 7‐fold greater among patients with clinically significant pocket hematoma versus those without ( P <0.001) 14. Further, results from BRUISE CONTROL advanced the literature beyond previously inconsistent findings on the association between hematoma and infection 15, 16, 17, 18, 19…”
Section: Introductionmentioning
confidence: 96%